Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Towards Sovereign Games - LaPensée, Elizabeth A.; Laiti, Outi; Longboat, Maize (Games and Culture, 2021)
Video games can be dynamic sovereign spaces for Indigenous representation and expression when the self-determination of Indigenous people is supported. Where ga...
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé